Influence of Physical Activity and Nutrition on Obesity-Related Immune Function - Chun-Jung Huang; Michael C. Zourdos; Edward Jo; Michael J. Ormsbee (The Scientific World Journal)
Research examining immune function during obesity suggests that excessive adiposity is linked to impaired immune responses leading to pathology. The deleterious effects of obesity on immunity have been associated with the systemic proinflammatory profile generated by the secretory molecules derived from adipose cells. These include inflammatory peptides, such as TNF-α, CRP, and IL-6. Consequently, obesity is now characterized as a state of chronic low-grade systemic inflammation, a condition considerably linked to the development of comorbidity. Given the critical role of adipose tissue in the inflammatory process, especially in obese individuals, it becomes an important clinical objective to identify lifestyle factors that may affect the obesity-immune system relationship. For instance, stress, physical activity, and nutrition have each shown to be a significant lifestyle factor influencing the inflammatory profile associated with the state of obesity. Therefore, the purpose of this review is to comprehensively evaluate the impact of lifestyle factors, in particular psychological stress, physical activity, and nutrition, on obesity-related immune function with specific focus on inflammation.